A Revolution in Economic Theory? - Kaysen, Carl (Review of Economic Studies, 1946)
Journal Article A Revolution in Economic Theory? Get access Carl Kaysen Carl Kaysen Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 1, 1946, Pages 1–15, https://doi.org/10.2307/2295753 Published: 01 April 1946